Infeksi Cacing Pita pada Anjing Bali dan Gambaran Morfologinya (TAPE WORM INFECTION IN BALI DOGS AND THEIR MORPHOLOGICAL DESCRIPTION) - Dharmawan, Nyoman Sadra; Suratma, Nyoman Adi; Damriyasa, Made; Merdana, I Made (Jurnal Veteriner; Vol 4 No 1 (2003), 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: tape worm, bali dogs, morphology